Emotions and Coping Strategies During Breast Cancer in Latina Women: A Focus Group Study. (September 2019) - Castillo, Anabel; Mendiola, Jennifer; Tiemensma, Jitske
We conducted three focus groups among Latina breast cancer (BC) survivors ( N = 23). The aim was to qualitatively identify how Latina women cope with BC treatment, what emotions arose during their treatment, and if they experienced any medical barriers during their journey. Women were also asked about a potential online resource. Specific emotions of anger and fear were commonly identified but related to different contexts. Family support and spirituality were frequently cited as two positive coping resources during BC and its treatment. Additionally, women expressed what they believe would be essential in an online community that would provide aid with BC support. Given the importance of reaching this vulnerable minority group, we recommend that future studies contextualize Latina women's emotional experiences and coping skills associated with BC as indicators of well-being. Along with previous studies, this study highlights the importance of developing culturally appropriate interventions. Additionally, we address alternative forms of resources that may be more accessible.